Anti-adhesion coating liquid and preparation method thereof, hardened film and preparation method thereof, polarizer

By using anti-adhesion coating liquid on the polarizer to form a hardened film, the adhesion problem of polarizer in liquid crystal display applications is solved, the warping and winding performance is improved, and the overall performance is achieved.

CN116694227BActive Publication Date: 2024-12-27NINGBO HUGHSTAR ADVANCED MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310772287.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-27
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

In the application of existing polarizers in LCD screens, the lack of concave and convex structure of the transparent hardened film leads to prone to adhesion during the roll-to-roll production process, resulting in problems such as indentation and ribs, especially after the base film is thinned. obvious.

Method used

A kind of anti-adhesion coating liquid is adopted, including thermoplastic resin, double curing resin, main resin, monomer, photoinitiator, nanomaterial and solvent, and the hardened film is formed by thermal curing and photocuring, which improves anti-adhesion effect and improves warping height and Collection issues.

Benefits of technology

The surface flatness and low warping of the hardened film are achieved, reducing indentation and tensile problems during the winding process, and improving the overall performance of the polarizer.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application provides an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof, and a polarizer, and belongs to the technical field of display screens. The anti-adhesion coating liquid includes 0.5 to 10 parts by mass of a thermoplastic resin and 0 to 10 parts by mass of a dual-curing resin. The present application adds a thermoplastic resin to the anti-adhesion coating liquid, and the thermoplastic resin has the effect of rapid surface drying, so that the thermoplastic resin can act as a film-forming aid in the anti-adhesion coating liquid, so that the anti-adhesion coating liquid can be quickly partially film-formed before thermal curing, and in the process of partial film formation, part of the nanomaterial can be brought out and float on the surface of the anti-adhesion coating liquid, effectively improving the anti-adhesion effect of the anti-adhesion coating liquid after application, and is suitable for thin base films. In addition, the thermoplastic resin can improve the film-forming effect of the anti-adhesion coating liquid, making it more dense and smooth before light curing, improving the high warping of the obtained hardened film, and the problems of indentation and tendon tension during the winding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of display screens, and in particular to an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof, and a polarizer. Background Art

[0002] Existing polarizers are usually functionalized when used in liquid crystal displays. As the overall thickness of the display screen becomes thinner and thinner, the thickness of the polarizers is also gradually becoming thinner to meet display requirements and process conditions.

[0003] At present, the surface treatment of polarizers can be roughly divided into anti-glare functional type and transparent hardening. Transparent hardening does not have the concave-convex structure of the anti-glare film surface. In the roll-to-roll production process, it is easy to cause adhesion due to the characteristics of the material, resulting in many undesirable problems such as indentation and rib tension. The thinner the base film, the more obvious the problem. Summary of the invention

[0004] The present application provides an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof, and a polarizer, which can improve the high warping of the hardened film, as well as the indentation and tension problems during the winding process.

[0005] The embodiment of the present application is implemented as follows:

[0006] In the first aspect, the present application example provides an anti-adhesion coating liquid, which includes: 0.5 to 10 parts by mass of thermoplastic resin, 0 to 10 parts by mass of dual-cure resin, 5 to 30 parts by mass of main resin, 2 to 10 parts by mass of monomer, 0.21 to 3.6 parts by mass of photoinitiator, 0.5 to 20 parts by mass of nanomaterial and 20 to 400 parts by mass of solvent.

[0007] In the above technical solution, the present application adds a thermoplastic resin to the anti-adhesion coating liquid, and the thermoplastic resin has the effect of rapid surface drying, so that the thermoplastic resin can act as a film-forming aid in the anti-adhesion coating liquid, and then the anti-adhesion coating liquid can quickly partially form a film before thermal curing, and in the process of partial film formation, part of the nanomaterial can be brought out and float on the surface of the anti-adhesion coating liquid, effectively improving the anti-adhesion effect of the anti-adhesion coating liquid after application, and is suitable for thin base films. In addition, the thermoplastic resin can improve the film-forming effect of the anti-adhesion coating liquid, making it denser and smoother before light curing, improving the high warping of the hardened film obtained, and the problems of indentation and tendon tension during the winding process.

[0008] In combination with the first aspect, in a first possible example of the first aspect of the present application, the viscosity of the thermoplastic resin is 10000 cps-500000 cps.

[0009] Optionally, the thermoplastic resin includes a thermoplastic acrylic resin and / or a thermoplastic polyurethane elastomer.

[0010] In the above example, the thermoplastic resin with a viscosity of 10000 cps-500000 cps has a fast surface drying effect, so that the thermoplastic resin can act as a film-forming aid in the anti-adhesion coating liquid, thereby allowing the anti-adhesion coating liquid to quickly partially form a film before thermal curing.

[0011] In combination with the first aspect, in a second possible example of the first aspect of the present application, the above-mentioned anti-adhesion coating includes: 1 to 5 parts by mass of thermoplastic resin, 0 to 5 parts by mass of dual-cure resin, 10 to 25 parts by mass of main resin, 2.5 to 7.5 parts by mass of monomer, 0.28 to 3.2 parts by mass of photoinitiator, 1 to 10 parts by mass of nanomaterial and 40 to 200 parts by mass of solvent.

[0012] Optionally, the main resin includes any one or more of polyurethane acrylic resin, silicone acrylic resin and polyester acrylic resin.

[0013] Optionally, the monomer includes any one or more of pentaerythritol hexaacrylate, pentaerythritol triacrylate, ethoxyethyl acrylate, trihydroxymethylpropane triacrylate, hexanediol diacrylate, and propoxypentanediol diacrylate.

[0014] Optionally, the photoinitiator comprises a cleavage-type photoinitiator.

[0015] Optionally, the cleavage-type photoinitiator includes any one or more of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0016] Optionally, the nanomaterial includes nanosol or nanoparticles, the nanosol includes any one or more of silica sol, aluminum sol and zirconium sol, and the nanoparticles include any one or more of silicon oxide, aluminum oxide and zirconium oxide.

[0017] Optionally, the solvent includes any one or more of methyl isobutyl ketone, propylene glycol methyl ether acetate, propylene glycol butyl ether, ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether and dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.

[0018] In combination with the first aspect, in a third possible example of the first aspect of the present application, the anti-adhesion coating liquid includes 0.1 to 5 parts by mass of a dual-cure resin.

[0019] Optionally, the dual-cure resin includes a hydroxyl-modified UV light-curable resin.

[0020] Optionally, the hydroxyl-modified UV light-curable resin includes a hydroxyl-modified polyester acrylic resin or a hydroxyl-modified polyurethane acrylic resin.

[0021] In the above example, the dual-cure resin can be combined with the thermoplastic resin to further improve the anti-adhesion effect after the application of the anti-adhesion coating, improve the high warping of the obtained hardened film, and improve the indentation and tension problems during the winding process.

[0022] In a second aspect, the present application provides a method for preparing the anti-adhesion coating of the above-mentioned embodiment, which comprises: mixing a thermoplastic resin, a dual-cure resin and a solvent to prepare a first mixture, and then mixing the first mixture, a main resin, a monomer, a photoinitiator and a nanomaterial to prepare the anti-adhesion coating.

[0023] In the above technical solution, the preparation method of the anti-adhesion coating liquid of the present application is simple, and the prepared anti-adhesion coating liquid is stable.

[0024] In a third aspect, the present application provides a hardened film, which includes a base film and an anti-adhesion layer arranged in a stacked manner, wherein the anti-adhesion layer is formed by curing the anti-adhesion coating liquid of the above embodiment.

[0025] In the above technical solution, the surface of the hardened film of the present application is smooth, the warping is low, and it can achieve good winding, with basically no problems such as indentation and rib tension.

[0026] In combination with the third aspect, in a first possible example of the third aspect of the present application, the material of the base film includes TAC, PET, PMMA, PC or COP.

[0027] In combination with the third aspect, in a second possible example of the third aspect of the present application, the thickness of the anti-adhesion layer is 1 μm to 5 μm.

[0028] In the above example, the anti-adhesion layer is relatively thin, which is suitable for a thin base film for preparing a thin polarizer.

[0029] In a fourth aspect, the present application provides a method for preparing the hardened film of the above-mentioned embodiment, which comprises: coating the anti-adhesion coating liquid on the surface of the base film, before thermal curing, the anti-adhesion coating liquid forms a film on the surface within a time of ≤20s to form a preformed product, and then the preform is subjected to thermal curing and photocuring in sequence to form a hardened film.

[0030] In the above technical scheme, before thermal curing, the thermoplastic resin in the anti-adhesion coating can enable part of the nanomaterials to be brought out and float on the surface of the anti-adhesion coating within 20 seconds, while quickly forming a surface film, and during the thermal curing process, the amount of nanomaterials floating on the surface of the anti-adhesion coating is further increased, thereby improving the anti-adhesion effect after the application of the anti-adhesion coating.

[0031] In a fifth aspect, the present application provides a polarizer, which includes the hardened film in the above embodiment. DETAILED DESCRIPTION

[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] The following is a specific description of an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof, and a polarizer in an embodiment of the present application:

[0034] The present application provides an anti-adhesion coating liquid, which includes: 0.5 to 10 parts by mass of a thermoplastic resin, 0 to 10 parts by mass of a dual-cure resin, 5 to 30 parts by mass of a main resin, 2 to 10 parts by mass of a monomer, 0.21 to 3.6 parts by mass of a photoinitiator, 0.5 to 20 parts by mass of a nanomaterial and 20 to 400 parts by mass of a solvent.

[0035] The viscosity of the thermoplastic resin is 10000cps-500000cps.

[0036] Thermoplastic resins with a viscosity of 10,000 cps to 500,000 cps have a rapid surface drying effect, so that the thermoplastic resin can act as a film-forming aid in the anti-adhesion coating liquid, thereby allowing the anti-adhesion coating liquid to quickly partially form a film before thermal curing.

[0037] Optionally, the thermoplastic resin includes a thermoplastic acrylic resin and / or a thermoplastic polyurethane elastomer.

[0038] Dual-cure resins include hydroxyl-modified UV light-curable resins.

[0039] Optionally, the hydroxyl-modified UV light-curable resin includes a hydroxyl-modified polyester acrylic resin or a hydroxyl-modified polyurethane acrylic resin.

[0040] Optionally, the mass ratio of the thermoplastic resin to the dual-cure resin is 1:(0-4), and the total mass of the thermoplastic resin and the dual-cure resin does not exceed 50% of the total mass of the main resin and the monomer.

[0041] As an example, the anti-adhesion coating may not contain dual-cure resin, or the mass ratio of thermoplastic resin to dual-cure resin may be 1:0.1, 1:0.2, 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.

[0042] Optionally, the mass ratio of the thermoplastic resin to the dual-cure resin is 1:(0-3).

[0043] Optionally, the anti-adhesion coating liquid includes 0.1 to 5 parts by mass of a dual-cure resin.

[0044] Dual-cure resin can be combined with thermoplastic resin to further improve the anti-adhesion effect after the application of the anti-adhesion coating, improve the high warping of the obtained hardened film, and the indentation and tension problems during the winding process.

[0045] The main resin includes any one or more of polyurethane acrylic resin, silicone acrylic resin and polyester acrylic resin.

[0046] The monomer includes any one or more of pentaerythritol hexaacrylate, pentaerythritol triacrylate, ethoxyethyl acrylate, trihydroxymethyl propane triacrylate, hexanediol diacrylate, and propoxypentanediol diacrylate.

[0047] The photoinitiator includes a cleavage-type photoinitiator.

[0048] Optionally, the cleavage-type photoinitiator includes any one or more of 2-hydroxy-2-methylpropiophenone (photoinitiator 1173), 1-hydroxycyclohexylphenyl ketone (photoinitiator 184), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (photoinitiator 907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone (photoinitiator 369) and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819).

[0049] Optionally, the mass of the photoinitiator is 3% to 9% of the mass of the main resin and the monomer.

[0050] As an example, the mass of the photoinitiator may be 3%, 4%, 5%, 6%, 7%, 8% or 9% of the mass of the main resin and the monomer.

[0051] Optionally, the mass of the photoinitiator is 4% to 8% of the mass of the main resin and the monomer.

[0052] The nanomaterial includes nanosol or nanoparticles. The nanosol includes any one or more of silica sol, aluminum sol and zirconium sol. The nanoparticles include any one or more of silicon oxide, aluminum oxide and zirconium oxide.

[0053] Optionally, the mass of the nanomaterial is 25% to 200% of the mass of the monomer.

[0054] As an example, the mass of the nanomaterial is 25%, 50%, 80%, 100%, 120%, 150%, 180% or 200% of the mass of the monomer.

[0055] Optionally, the mass of the nanomaterial is 50% to 100% of the mass of the monomer.

[0056] Optionally, the particle size of the nanomaterial is 10nm to 1000nm.

[0057] Optionally, the particle size of the nanomaterial is 30nm to 100nm.

[0058] The solvent includes any one or more of methyl isobutyl ketone, propylene glycol methyl ether acetate, propylene glycol butyl ether, ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether and dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.

[0059] Optionally, the anti-adhesion coating includes: 1 to 5 parts by mass of thermoplastic resin, 0 to 5 parts by mass of dual-cure resin, 10 to 25 parts by mass of main resin, 2.5 to 7.5 parts by mass of monomer, 0.28 to 3.2 parts by mass of photoinitiator, 1 to 10 parts by mass of nanomaterial and 40 to 200 parts by mass of solvent.

[0060] The present application adds a thermoplastic resin to the anti-adhesion coating liquid, and the thermoplastic resin has the effect of rapid surface drying, so that the thermoplastic resin can act as a film-forming aid in the anti-adhesion coating liquid, and then the anti-adhesion coating liquid can quickly partially form a film before thermal curing, and in the process of partial film formation, part of the nanomaterial can be brought out and float on the surface of the anti-adhesion coating liquid, effectively improving the anti-adhesion effect of the anti-adhesion coating liquid after application, and is suitable for thin base films. In addition, the thermoplastic resin can improve the film-forming effect of the anti-adhesion coating liquid, making it denser and smoother before light curing, improving the high warping of the hardened film obtained, and the problems of indentation and tendon tension during the winding process.

[0061] The present application also provides a method for preparing the anti-adhesion coating of the above embodiment, which comprises: mixing a thermoplastic resin, a dual-cure resin and a solvent to obtain a first mixture, and then mixing the first mixture, a main resin, a monomer, a photoinitiator and a nanomaterial to obtain the anti-adhesion coating.

[0062] Optionally, the solid content of the first mixture is 0.1% to 25%.

[0063] Optionally, the solid content of the first mixture is 0.5% to 15%.

[0064] The preparation method of the anti-adhesion coating liquid of the present application is simple, and the prepared anti-adhesion coating liquid is stable.

[0065] The present application also provides a hardened film, which includes a base film and an anti-adhesion layer which are stacked, and the anti-adhesion layer is formed by curing the anti-adhesion coating liquid of the above embodiment.

[0066] The materials of the base film include TAC, PET, PMMA, PC or COP.

[0067] The thickness of the anti-adhesion layer is 1 μm to 5 μm.

[0068] As an example, the thickness of the anti-adhesion layer may be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0069] Optionally, the thickness of the anti-adhesion layer is 1.5 μm to 3 μm.

[0070] The anti-adhesion layer is relatively thin and is suitable for thin base films used to prepare thin polarizers.

[0071] The hardened film of the present application has a smooth surface, low warping, and can be rolled up well, with basically no problems such as indentation and rib tension.

[0072] The present application also provides a method for preparing a hardened film of an embodiment, which includes: coating an anti-adhesion coating liquid on the surface of a base film, before thermal curing, forming a film of the anti-adhesion coating liquid on the surface within a time of ≤20s to form a preformed product, and then sequentially subjecting the preform to thermal curing and photocuring to form a hardened film.

[0073] The thermal curing is carried out in an oven. In the process of transporting the base film coated with the anti-adhesion coating liquid to the oven, the anti-adhesion coating liquid can form a film on the surface within a time of ≤20s.

[0074] Optionally, the anti-adhesion coating liquid forms a film on the surface within a time of ≤10 s.

[0075] Optionally, the anti-adhesion coating liquid forms a film on the surface within a time of ≤5 s.

[0076] The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 60° C. to 100° C. for 1 minute to 4 minutes.

[0077] Light curing is carried out under light conditions, and the light intensity is 200mJ / cm 2 ~500mJ / cm 2 .

[0078] Before thermal curing, the anti-adhesion coating can form a film on the surface within 20 seconds, so that part of the nanomaterial can be brought out and float on the surface of the anti-adhesion coating. During the thermal curing process, the amount of nanomaterials floating on the surface of the anti-adhesion coating is further increased, thereby improving the anti-adhesion effect after the application of the anti-adhesion coating.

[0079] The present application also provides a polarizer, which includes the hardened film in the above embodiment.

[0080] Furthermore, the polarizer includes the hardened film and the polarized substrate in the above embodiment, wherein the hardened film is attached to the surface of the polarized substrate, and the hardened film and the polarized substrate have a good bonding effect. Before bonding, alkaline washing of the hardened film will basically not affect the performance of the hardened film.

[0081] Optionally, the polarizing substrate is a polyvinyl alcohol film, which can be well bonded to the hardened film after alkali washing. The thickness of the polarizer in the present application can be further reduced as the thickness of the hardened film used is reduced, and the hardened coating has strong alkali washing resistance, and has better hardness, scratch resistance and texture appearance.

[0082] Optionally, the base film used for the hardened film has a thickness of 12 μm to 25 μm.

[0083] Optionally, the base film used for the hardened film has a thickness of 12 μm or 25 μm.

[0084] The following is a further detailed description of an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof of the present application in conjunction with embodiments.

[0085] Example 1

[0086] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0087] S1. Preparation of anti-adhesion coating solution

[0088] 2.5 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0089] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0090] S2. Preparation of hardened film

[0091] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0092] Example 2

[0093] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0094] S1. Preparation of anti-adhesion coating solution

[0095] 10 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0096] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0097] S2. Preparation of hardened film

[0098] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0099] Example 3

[0100] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0101] S1. Preparation of anti-adhesion coating solution

[0102] 0.5 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0103] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0104] S2. Preparation of hardened film

[0105] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0106] Example 4

[0107] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0108] S1. Preparation of anti-adhesion coating solution

[0109] 2.5 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0110] 20 parts by mass of Sartomer CN9001NS (main resin), 3 parts by mass of Changxing Chemical EM265 (monomer), 2 parts by mass of Wuxi Sinopharm Chemical GM63F0H (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0111] S2. Preparation of hardened film

[0112] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0113] Example 5

[0114] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0115] S1. Preparation of anti-adhesion coating solution

[0116] 2.5 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0117] 20 parts by mass of Sinopharm Chemical UX-9001W (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0118] S2. Preparation of hardened film

[0119] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0120] Example 6

[0121] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0122] S1. Preparation of anti-adhesion coating solution

[0123] 1.875 parts by mass of thermoplastic polyurethane elastomer, 0.625 parts by mass of Shanghai Sifeng Technology SUO-1881N (dual-cure resin), 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0124] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0125] S2. Preparation of hardened film

[0126] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0127] Example 7

[0128] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0129] S1. Preparation of anti-adhesion coating solution

[0130] 1.25 parts by mass of thermoplastic polyurethane elastomer, 1.25 parts by mass of Shanghai Sifeng Technology SUO-1881N (dual-cure resin), 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0131] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0132] S2. Preparation of hardened film

[0133] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0134] Example 8

[0135] The embodiments of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0136] S1. Preparation of anti-adhesion coating solution

[0137] 0.625 parts by mass of thermoplastic polyurethane elastomer, 1.875 parts by mass of Shanghai Sifeng Technology SUO-1881N (dual-cure resin), 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0138] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0139] S2. Preparation of hardened film

[0140] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0141] Comparative Example 1

[0142] The comparative examples of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0143] S1. Preparation of anti-adhesion coating solution

[0144] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare an anti-adhesion coating liquid.

[0145] S2. Preparation of hardened film

[0146] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0147] Comparative Example 2

[0148] The comparative examples of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0149] S1. Preparation of anti-adhesion coating solution

[0150] 2.5 parts by mass of Shanghai Sifeng Technology SUO-1881N (dual-cure resin), 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0151] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0152] S2. Preparation of hardened film

[0153] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0154] Comparative Example 3

[0155] The comparative examples of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0156] 15 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0157] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2.5 parts by mass of nano-silica and the prepared film-forming aid were mixed and stirred evenly to prepare an anti-adhesion coating liquid.

[0158] S2. Preparation of hardened film

[0159] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0160] Comparative Example 4

[0161] The comparative examples of the present application provide an anti-adhesion coating liquid and a preparation method thereof, a hardened film and a preparation method thereof.

[0162] S1. Preparation of anti-adhesion coating solution

[0163] 2.5 parts by mass of thermoplastic polyurethane elastomer, 10 parts by mass of butanone, 6 parts by mass of propylene glycol methyl ether, 2.5 parts by mass of propylene glycol methyl ether acetate and 50 parts by mass of methyl isobutyl ketone were mixed and stirred uniformly to prepare a film-forming aid.

[0164] 20 parts by mass of Sartomer CN9001NS (main resin), 5 parts by mass of Changxing Chemical EM265 (monomer), 1.6 parts by mass of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184) and the prepared film-forming aid were mixed and stirred uniformly to prepare an anti-adhesion coating liquid.

[0165] S2. Preparation of hardened film

[0166] The prepared anti-adhesion coating liquid is coated on the surface of the base film, the base film is TAC with a thickness of 25 μm, and the anti-adhesion coating liquid forms a film on the surface within ≤5 seconds to form a preform, and then the preform is subjected to thermal curing and light curing in sequence. The thermal curing includes thermally curing the base film coated with the anti-adhesion coating liquid at 80°C for 2 minutes, and the light curing is carried out under light conditions, and the light intensity is 300 mJ / cm 2 , forming a cured film, and the thickness of the anti-adhesion layer formed by the anti-adhesion coating liquid is 3μm.

[0167] Test Example 1

[0168] The anti-adhesion effect, warping effect and rolling condition of the cured films of Examples 1 to 8 and Comparative Examples 1 to 4 were measured respectively, and the results are shown in Table 1.

[0169] Among them, the test method for the anti-adhesion effect is: put the hardened surface of the hardened film on the surface and rub it. If it can be rubbed and is very smooth, it is strong AB (anti-blocking); if it can be rubbed and is slightly astringent, it is weak AB; if it cannot be rubbed and is astringent, it is no AB.

[0170] Testing method for warping effect: Cut the hardened film into a 100mm*100mm square, place it with the hardened surface facing upwards, and measure its side length > 80mm, which indicates a good warping effect.

[0171] Test method for coiling condition: After 1000m coil is placed for 14 days, the problem points are observed with naked eyes. Indentation indicates abnormality after placement, and tension indicates abnormality at the end of production.

[0172] Table 1 Properties of the cured films of Examples 1 to 8 and Comparative Examples 1 to 4

[0173] project Anti-adhesion effect Warping effect Rolling situation Example 1 Weak AB >80mm No abnormality Example 2 Weak AB >80mm No abnormality Example 3 Weak AB >80mm No abnormality Example 4 Weak AB >80mm No abnormality Example 5 Weak AB >80mm No abnormality Example 6 Strong AB >80mm No abnormality Example 7 Strong AB >80mm No abnormality Example 8 Strong AB >80mm No abnormality Comparative Example 1 Weak AB 70mm Indentation Comparative Example 2 Weak AB >80mm Slight muscle tension Comparative Example 3 Weak AB >80mm No abnormality Comparative Example 4 No AB 55mm Indentation, tendon stretch

[0174] From the comparison between Example 1 and Examples 6 to 8, it can be seen that when the dual-cure resin is added to the anti-adhesion coating liquid, the dual-cure resin can be combined with the thermoplastic resin to further improve the anti-adhesion effect of the anti-adhesion coating liquid after application.

[0175] From the comparison between Example 1 and Comparative Example 1, it can be seen that the anti-adhesion coating of Comparative Example 1 does not contain thermoplastic resin. Although it has a certain anti-adhesion AB, indentations will appear after being rolled up. This is because the nanomaterials in the anti-adhesion coating rely solely on solvents, and only a small part of them float on the coating surface during the actual production process.

[0176] From the comparison between Example 1 and Comparative Example 2, it can be seen that the anti-adhesion coating of Comparative Example 2 does not contain thermoplastic resin, but only contains dual-curing resin. Although it has a certain anti-adhesion AB, the surface of the anti-adhesion layer is not smooth enough, and it is easy to cause tendon tension problems due to tension line problems.

[0177] From the comparison between Example 1 and Comparative Example 3, it can be seen that the anti-adhesion coating of Comparative Example 3 contains an excessive amount of thermoplastic resin. Although the AB effect, warping and winding effects are achieved, the inventors found that in actual use, excessive addition of thermoplastic elastomer will cause the thermoplastic elastomer to precipitate, affecting the service life of the product.

[0178] From the comparison between Example 1 and Comparative Example 4, it can be seen that Comparative Example 4 does not contain nanomaterials, has no anti-adhesion AB at all, and has very poor warping and rolling problems.

[0179] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An anti-adhesion coating liquid, characterized in that: The anti-adhesion coating liquid comprises: 0.5 to 10 parts by mass of thermoplastic resin, 0.1 to 5 parts by mass of dual-curing resin, 5 to 30 parts by mass of main resin, 2 to 10 parts by mass of monomer, 0.21 to 3.6 parts by mass of photoinitiator, 0.5 to 20 parts by mass of nanomaterial and 20 to 400 parts by mass of solvent; The thermoplastic resin includes a thermoplastic acrylic resin and / or a thermoplastic polyurethane elastomer, and the viscosity of the thermoplastic resin is 10000cps-500000cps; The dual-curing resin includes a hydroxyl-modified UV light-curing resin, and the hydroxyl-modified UV light-curing resin includes a hydroxyl-modified polyester acrylic resin or a hydroxyl-modified polyurethane acrylic resin; The main resin includes any one or more of polyurethane acrylic resin, silicone acrylic resin and polyester acrylic resin.

2. The anti-adhesion coating liquid according to claim 1, characterized in that: The anti-adhesion coating liquid comprises: 1 to 5 parts by mass of thermoplastic resin, 0.1 to 5 parts by mass of dual-curing resin, 10 to 25 parts by mass of main resin, 2.5 to 7.5 parts by mass of monomer, 0.28 to 3.2 parts by mass of photoinitiator, 1 to 10 parts by mass of nanomaterial and 40 to 200 parts by mass of solvent.

3. The anti-adhesion coating liquid according to claim 2, characterized in that: The monomer includes any one or more of pentaerythritol hexaacrylate, pentaerythritol triacrylate, ethoxyethyl acrylate, trihydroxymethylpropane triacrylate, hexanediol diacrylate and propoxypentanediol diacrylate.

4. The anti-adhesion coating according to claim 2, characterized in that: The photoinitiator includes a cleavage-type photoinitiator.

5. The anti-adhesion coating liquid according to claim 4, characterized in that: The cleavage-type photoinitiator includes any one or more of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

6. The anti-adhesion coating liquid according to claim 2, characterized in that: The nanomaterial includes nanosol or nanoparticles, the nanosol includes any one or more of silica sol, aluminum sol and zirconium sol, and the nanoparticles include any one or more of silicon oxide, aluminum oxide and zirconium oxide.

7. The anti-adhesion coating liquid according to claim 2, characterized in that: The solvent includes any one or more of methyl isobutyl ketone, propylene glycol methyl ether acetate, propylene glycol butyl ether, ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether and dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.

8. A method for preparing the anti-adhesion coating liquid according to any one of claims 1 to 7, characterized in that: The preparation method of the anti-adhesion coating liquid comprises: mixing the thermoplastic resin, the dual-cure resin and the solvent to obtain a first mixture, and then mixing the first mixture, the main resin, the monomer, the photoinitiator and the nanomaterial to obtain the anti-adhesion coating liquid.

9. A hardened film, characterized in that: The hardened film comprises a base film and an anti-adhesion layer which are stacked, and the anti-adhesion layer is formed by curing the anti-adhesion coating liquid according to any one of claims 1 to 7.

10. The hardened film according to claim 9, characterized in that: The material of the base film includes TAC, PET, PMMA, PC or COP.

11. The hardened film according to claim 9, characterized in that: The thickness of the anti-adhesion layer is 1 μm to 5 μm.

12. A method for preparing a hardened film according to any one of claims 9 to 11, characterized in that: The preparation method of the hardened film comprises: coating the anti-adhesion coating liquid on the surface of the base film, before thermal curing, the anti-adhesion coating liquid forms a film on the surface within a time of ≤20s to form a preform, and then the preform is thermally cured and photocured in sequence to form the hardened film.

13. A polarizer, characterized in that: The polarizer includes the cured film according to any one of claims 9 to 11.